Transformation-induced strain of a low transformation temperature alloy with high hardness during laser metal deposition. (August 2021) - Fang, J.X.; Ma, G.Z.; Tian, H.L.; Li, S.B.; Huang, H.S.; Liu, Y.; Jiang, Y.L.; Liu, B.
Abstract: Bulk crack-free Fe-Cr-Ni-Mo-Si-B alloy (with high hardness of 54.5 HRC) was fabricated via laser metal deposition (LMD). The solid-state phase transformation (PT) volume effect, transformation-induced plasticity (TRIP), and the influences of PT strain on the tensile properties of Fe-Cr-Ni-Mo-Si-B alloy were investigated, and the problem of how to release thermal contraction through PT strain in the LMD process was discussed. The results show that the volume strain of the martensite PT of Fe-Cr-Ni-Mo-Si-B alloy was equivalent to the thermal contraction strain caused by a temperature decrease of about 370 °C for the austenite of this alloy, and the PT volume expansion effect increased with a decrease in transformation temperature. In the LMD process, the Magee effect had an obvious contribution on the TRIP, but the decrease of tensile stress during the actual PT process must be considered. Under constant load conditions close to the yield strength, the strain of TRIP should be an order of magnitude higher than that of the transition volume effect. In situ neutron diffraction demonstrated that the martensite starting point ( M s ) of PT can be significantly increased by stress and plastic. The highest martensite starting temperature of strain induced PT ( M d ) is about 360 °C higher than that of PT without external stress. PT strain can endow the materials, which are completely brittle at room temperature, with an elongation up to 34% in the tensile process. Thermal contraction strain the LMD process can be counteracted by PT strain, thus achieving the crack-free formation of high-hardness materials. Highlights: PT strain is dominated by PT temp, stress level, plastic deformation etc. PT strain can endow brittle materials at RT with a high elongation up to 34%. Thermal contraction strain in LMD can be counteracted by PT strain. Crack-free high-hardness materials can be fabricated with the aid of PT strain.